Anti-Inflammatory and Wound Healing Activity of Leaf Extracts of Cocculus Pendulus (J. R. & G. Forst.) Diels. - H. RABARI; S. PANDYA; G. VIDYASAGAR; B. GAJRA (International Journal of Pharma and Bio Sciences, 2010)
The chloroform and ethyl acetate extracts of leaves of Cocculus pendulus, were tested for anti-inflammatory and wound healing activity at the doses of 200 and 400 mg/kg body weight. Both the extracts at the dose of 400 mg/kg body weight, produced dose dependent and significant inhibition of carrageenan induced paw edema. The exhibited anti-inflammatory activity was comparable with the standard drug aspirin. The wound healing activity was evaluated by using excision wound model of rat. The percentage of wound contraction was found to be significant in animals treated with chloroform extract and ethyl acetate extract when compared to controls. The results were comparable with that of the standard drug povidone iodine ointment. The chloroform and ethyl acetate extract treated wounds were found to epithelize faster as compared to controls.